Management of Complex Zygomaticomaxillary Fracture with Frontal and Orbital Wall Involvement Associated with a Crushed Globe: A Case Report - Krishna Balaji Pampatwar; Bhushan Mundada; Nitin Bhola (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Zygomaticomaxillary Complex (ZMC) fractures are among the most common midfacial injuries and are frequently caused by highvelocity trauma, particularly road traffic accidents. These fractures frequently affect nearby structures including the orbit, maxilla, and frontal bone, leading to serious problems with function, appearance, and vision. To restore orbital integrity, facial symmetry, and functional outcomes, prompt diagnosis and appropriate surgical intervention are essential. A 17-year-old male presented with severe facial trauma following a road traffic accident. Significant facial asymmetry, periorbital oedema, flattening of the right malar prominence, limited jaw opening, and total loss of vision in the right eye were found during the clinical examination. An ophthalmological examination revealed a crushed globe that could not be saved. A complicated right-sided ZMC fracture involving the orbital floor, lateral orbital wall, maxillary sinus walls, along with frontal bone was identified on Computed Tomography (CT) imaging of the facial bones. Significant orbital damage and fracture fragment displacement were observed. Under general anaesthesia, the patient underwent a surgical procedure. Titanium miniplates and screws were used for open reduction and internal fixation of the frontal and zygomaticomaxillary bone fractures. In order to prevent enophthalmos and restore orbital support, titanium mesh was used for orbital floor repair. Because of the permanent ocular lesion, the injured globe was eviscerated. The face contour was well restored, the mouth opening was better, the occlusion was stable, with wounds healing appropriately. The postoperative recovery was uncomplicated. In order to manage difficult midfacial fractures for the best possible functional and cosmetic rehabilitation, this case highlights the significance of thorough clinical examination, radiographic assessment, and a multidisciplinary approach.